Objective rest–activity cycle analysis by actigraphy identifies isolated rapid eye movement sleep behavior disorder. (7th July 2020) - Filardi, M.; Stefani, A.; Holzknecht, E.; Pizza, F.; Plazzi, G.; Högl, B.
Abstract : Background and purpose: Isolated rapid eye movement (REM) sleep behavior disorder (iRBD) is characterized by abnormal behaviours during REM sleep. Several studies showed that iRBD is a prodromal stage of synucleinopathies. Therefore, identifying iRBD in the general population is of utmost importance. In this study, we explore whether the assessment of rest–activity rhythm features can distinguish patients with iRBD from patients with disorders characterized by other pathological motor activity during sleep and healthy controls. Methods: Nineteen patients with video‐polysomnographic diagnosis of iRBD, 39 patients with other disorders with motor activity during sleep [19 with restless leg syndrome (RLS) and 20 with untreated sleep apnea syndrome (SAS)] and 16 healthy controls underwent 2‐week actigraphy and video‐polysomnography, and completed REM sleep behavior disorder screening questionnaires. Non‐parametric analyses were applied to assess the rest–activity rhythm features. Results: Patients with iRBD showed lower sleep efficiency, increased estimated wake after sleep onset and increased frequency of prolonged activity bouts compared to those with RLS and controls, while no difference emerged compared with SAS patients. Moreover, patients with iRBD presented increased occurrence of estimated nap in comparison to those with RLS, those with SAS and controls. The I < O, a 24‐h measure that expresses the relationship between nocturnal and diurnal motor activity intensity, distinguished patients with iRBD from those with RLS, those with SAS and controls, with an area under the curve greater than that of REM sleep behavior disorder screening questionnaires. An I < O of 98.32 shows the best balance between sensitivity (63.2%) and specificity (89.1%). Discussion: The I < O index distinguished iRBD patients from those with other pathological motor activity during sleep and controls, confirming its use as an objective measure suitable to screen large at‐risk populations.